Aerification Effects on ‘Innovation’ Zoysiagrass Thatch and Quality - Jack Fry; Dani McFadden (Kansas Agricultural Experiment Station Research Reports, 2021)
When a thatch layer accumulates on turfgrass it can be detrimental to the stand. A field experiment was initiated to investigate aerification treatments and their influence on organic matter, quality, and color of ‘Innovation’ zoysiagrass that was sodded within the past year. Turfgrass that was intensely aerified had less organic matter content in the surface inch of the profile compared to turfgrass that was not aerified. Color was also enhanced in treatments receiving aerification compared to nonaerified turf, which may have been attributed to trending of higher nitrate content in aerified plots.
Keywords: aerification; Innovation; zoysiagrass